Teachers’ Perception and Inclusion of Children with Disabilities in Uganda: A Study of Regular Classrooms in Primary Schools of Tororo District (Direct Research Journal of Social Science and Educational Studies, 2024)
The research conducted in Tororo district examined the perception of teachers’ towards the inclusion of children with disabilities in primary schools. Utilizing a cross-sectional survey research design, both quantitative and qualitative approaches were employed to gather data from 74 respondents selected through simple random and purposive sampling techniques. The findings revealed a significant relationship between teachers' perception and the inclusion of learners with various disabilities in primary schools within Tororo District. Consequently, it was inferred that teachers' perception significantly influences the inclusion of learners with disabilities in the district's primary schools. The study recommended that school administrators should admit all children, including those with disabilities, without discrimination. Furthermore, it suggested the organization of refresher courses and seminars to equip teachers with the necessary skills for teaching children with diverse forms of disabilities. Additionally, the study proposed that the government of the Republic of Uganda, particularly through the Ministry of Education and Sports, invest more in providing accessible, disability-friendly learning environments and adapted specialized educational materials to facilitate inclusive learning in primary schools within Tororo District.
Keywords: Teacher perception; inclusion; children; disabilities; primary schools; Tororo District; Uganda